A QUANTITATIVE APPROACH TO PROFITABILITY RATIOS - Consuela DICU; Maria Daniela BONDOC; Mihaela Bianca POPESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2019)
The main objective of this paper was represented by the analysis of the performances reflected by the rates of profitability in the case of three companies in the milling and bakery sector. We carried out econometric processing for which we used the linear and the second-order regression functions. The intensity and type of the correlations between the variables were highlighted, by analysing the rates of economic, financial and commercial profitability in correlation with the factors of influence in the case of three companies in the milling and bakery sector. At the same time, through the results we obtained, we were able to make comparisons between the three analyzed companies. Statistical tests were used to verify the econometric models: Durbin Watson, Student (t), Fisher–Snedecor, X2.